A função social da educação para os empresários industriais da FIESP - Silva, Leonardo (2021)
This work studied the social function of education for FIESP; specifically, we tried to analyze how the theory of human capital, which postulates a determination of the economy through education was appropriated by industrial entrepreneurs in a context of structural capital crisis (MÉSZÁROS, 2002). In other words, we try to understand how industrial entrepreneurs organized around the Federation of Industries of the State of São Paulo relate to investment in education to the economic development of a country and access to employment and income for salaried workers. Through the analysis of opinion articles published in newspapers and on the institution's website, we tried to answer the following question: Is education for FIESP a factor of economic development? When carrying out the data survey, we found that the institution's publications on the subject of education are scarce. There are, for example, no ideologues in the public sphere that organically represent FIESP's positions on the national scene regarding the paths that education should take. The institution's positions which are part of this research from the 2000's onward, are usually made public with opinion pieces published in newspapers with the signature of the current president. However, it was concluded that industrial entrepreneurs defend investment in education as a way out of the condition of subordination to the international division of labor, and the problem of unemployment and social inequalities. We argue that this FIESP position implies an ideological form (LUKÁCS, 2010) for the institution to position itself in the class struggle in the context of neoliberal accumulation; thus, diverting the cause of exploitation to the issue of training the workforce as the source of social inequalities.